Advancing fair and sustainable trade: Strategies for G20 action in the wake of environmental regulations - Mahiques, Maria Victoria Arias; De Maria, Marcello; Park, Leonardo; Sancisi, Angeles; Papendieck, Sabine; Piñeiro, Valeria; de Oliveira, Susan Cesar; Illescas, Nelson; Nakagawa, Louise; Uehara, Thiago (T20 Brazil, 2024)
The new environmental regulations aimed at ensuring sustainable trade in commodity supply chains, exemplified by the EU Deforestation Regulation (EUDR), represent a significant step towards tackling global environmental issues such as climate change, deforestation, and biodiversity loss. However, international trade should not only be greener but also more just and inclusive, ensuring that the benefits and burdens of these measures are evenly shared among all countries and societal groups. Developing Countries (DCs) and Least Developed Countries (LDCs), but also certain vulnerable groups like smallholder farmers, risk being disproportionately affected by these new regulations, with potential detrimental effects on economic growth, human development, and integration within the global trade system. These obstacles stem from increased production costs, potential competitiveness loss and complex compliance requirements. This brief delves into these hurdles and outlines immediate actions that the G20 should undertake in response. Even though there is no one-size-fits-all solution, the G20 can provide guidelines to address these shared challenges in three critical dimensions: I. Participatory governance: fostering multilateralism, open participation mechanisms and polycentric institutions. II. Capacity building: funding technological infrastructure, supplying technical assistance and supporting transparency tools. III. Economic incentives: designing and implementing market mechanisms that promote sustainable production. The G20 must play a key role in outlining policy strategies that comprehensively integrate climate change, trade, and agrifood systems, and guarantee the participation of DCs and LDCs, in order to achieve SDGs worldwide.